Property law in a globalizing world - Lehavi, Amnon (Global law series., 2019)
Property Law in a Globalizing World identifies the paramount challenges that contemporary processes of globalization pose for the study and practice of property law. It offers a straightforward analysis of legal scenarios implicating cross-border property rights, covering a broad range of resources, from land, goods, and intangible financial assets, to intellectual property, data, and digital assets. This is the first scholarly book offering a detailed study of legal strategies that can decrease the gap between the domestic tenets of property law and the cross-border nature of markets, interpersonal networks, and technology. It shows how strategies of soft law, conflict of laws, harmonization and supranationalism rely to various degrees on cross-border property norms and institutions, and studies the proprietary features of security interests and priorities to assets in insolvency in a global setting. It also shows how digital technology such as blockchain can revolutionize the system of cross-border property rights.--